2019
DOI: 10.1371/journal.pone.0221789
|View full text |Cite|
|
Sign up to set email alerts
|

To keep or not to keep? Decision making in adolescent pregnancies in Jamestown, Ghana

Abstract: Background Jamestown, an urban coastal slum in Accra, Ghana, has one of the highest adolescent pregnancy rates in the country. We sought to understand the decision (to keep or terminate) factors and experiences surrounding adolescent pregnancies. Methods Thirty semi-structured indepth interviews were carried out among adolescents (aged 13–19 years) who had been pregnant at least once. Half of these were adolescent mothers and the other half had at least one past experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 33 publications
2
70
0
4
Order By: Relevance
“… 38 In addition, the study indicated that partners, predominantly men, created barriers to abortion-related care through withholding moral support or financial resources. 38 …”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“… 38 In addition, the study indicated that partners, predominantly men, created barriers to abortion-related care through withholding moral support or financial resources. 38 …”
Section: Methodsmentioning
confidence: 98%
“…Self-administered surveys Open access using smart technologies (eg, mobile apps/web-based apps), and audiovisual platforms, were rejected, as they require a level of literacy and internet/data connectivity inappropriate for the context. 38 Quantitative survey Respondent-driven sampling Respondent-driven sampling (RDS) was first conceptualised as an alternative to snowball sampling for populations less likely to participate in research, for whom there was no reliable sampling frame to conduct a simple random sample. 72 73 As there are no appropriate existing mechanisms to identify men through social distanced, mobile phone means, RDS was considered suitable.…”
Section: Mobile Methodsmentioning
confidence: 99%
See 3 more Smart Citations